Cardiovascular impact of preeclampsia on mother and offspring - Lazdam, M (2013)
Preeclampsia is one of the leading causes of maternal and fetal mortality and morbidity. Furthermore, women who have had preeclampsia have an increased risk of cardiovascular events over the next 10-15 years. Indeed, preeclampsia is associated with a four-fold increase in the risk of hypertension and double the risk of fatal and non fatal ischaemic heart disease and stroke. In addition, offspring born to preeclampsia are more likely to have higher blood pressure from childhood and stroke in later life. The risk to mother and offspring is greatest when preeclampsia is diagnosed at an earlier gestation, suggesting a more severe form of preeclampsia. As the long term cardiovascular risk to both mother and child is known from delivery, the main interest of my research was to identify key phenotypic variations in mothers and children during the years between the episode of preeclampsia and emergence of established cardiovascular disease, which might explain the link between the two conditions. This information could then be used to devise ways to identify subjects at greatest risk of later cardiovascular disease and to establish intermediate endpoints for future preventative interventions. Therefore, in a case control study, women diagnosed with preeclampsia between 1998 and 2003 and their offspring were recruited and underwent comprehensive cardiovascular and metabolic phenotyping. Furthermore, young adults born preterm to hypertensive pregnancy were also investigated in their twenties. The research demonstrates that early-onset preeclampsia, diagnosed before 34 weeks gestation, is associated with blood pressure patterns in mothers 6-13 years after pregnancy that are distinct from those seen following later-onset disease. Furthermore, there is evidence of distinct differences in cardiac, vascular and metabolic profiles in these individuals with women having evidence of increased arterial stiffness, changes in cardiac function and reduced capillary density. Preterm offspring of hypertensive pregnancies similarly have higher blood pressure than seen in those born following late-onset disease and, in young adult life, have reduced endothelial function and changes in cardiac size proportional to this dysfunction. This research demonstrates adverse cardiac and vascular remodelling after preeclampsia in mothers and offspring that are evident before the development of clinical cardiovascular disease. The identified differences in cardiac and vascular function may be useful as surrogate endpoints in future preventive trials.